Management of innovation: elements that influence it in a Brazilian public university - Rosa, Wellington Luiz de Oliveira da; Maehler, Alisson Eduardo (Revista de Administração da UFSM, 2019)
The aim of this qualitative study was to analyze the elements that influence the process of innovation management in a public university in southern Brazil. It was conducted semi-structured interviews with 19 questions to three groups: six university managers; six researchers with only scientific production (articles) and seven researchers with also technological production (patents). After transcribing the interviews, the content analysis was performed in MAXQDA 12 software (Verbi GmbH, Berlin, Germany). The lack of understanding of the legal part (17.6%) and bureaucratization in the transfer process (14.7%) were the most frequently reported difficulties in the process of technology transfer. After identifying the main elements of innovation management in a public university, we proposed a new model in which the research projects are developed in conjunction with the productive sector since the beggining of technological development. Public policies and management measures to facilitate the interaction between academia and the productive sector can facilitate technology transfer and, consequently, management of innovation.